Mutagenicity potential (affect) of new atraumatic restorative treatment (ART) material incorporated with Azadirachta indica (Neem) against Salmonella typhimurium - P. Divya Kumari; A. Veena Shetty; Shahnawaz Khijmatgar; Avidyuti Chowdhury; Edward Lynch; Chitta R. Chowdhury (Journal of Oral Biology and Craniofacial Research, 2019)
Background: The mutagenicity potential of a new atraumatic restorative treatment (ART) material against Salmonella typhimurium without metabolic activity using the Ames test (genotoxicity) was carried out. Methods and materials: The potential mutagenicity of new atraumatic restorative treatment materials (ART-I and ART-II) was analyzed using the Ames test. The materials were eluted in dimethyl sulphoxide, 0.9% NaCl solution and sterilized de-ionized water and the aliquots were used after an incubation period of 24 h at 37 °C. Mutagenic effects of the materials were tested on Salmonella typhimurium strains TA 98 and TA 100 using the standard assay, and in absence of S9 fraction from rat liver. Result: No mutagenic effects were detected for these new ART materials on S. typhimurium TA100. The incubated DMSO extract and 0.9% NaCl extract (50 μl/plate) of the ART-I exhibited a weak mutagenic potential on S. typhimurium TA 98. In particular, Aqua extract (50 μl/plate) of ART-II, was associated with a weak mutagenic potential on S. typhimurium TA98. Conclusion: Both ART materials (ART–I and II) exhibited weak mutagenic effects on S. typhimurium TA98 whereas no mutagenic effect was detected on S. typhimurium TA100. ART-II is safer than ART-I.